2019
DOI: 10.5812/aapm.92672
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Self-Management Program on Pain and Disability Index in Elderly Men with Osteoarthritis

Abstract: Background: Osteoarthritis (OA) is a progressive disease of the joints, leading to decreased function and disability. Objectives: The study aimed to investigate the effect of self-management (SM) program on disability index and pain in aging men with knee OA. Methods: The study included an SM group and a control group. Given the sample size of the previous studies, 83 patients were recruited. The study tools included a demographic profile questionnaire, visual analogue scale (VAS), and HAQ 8-item DI. The inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…Cognitivebehavioral therapy interventions are effective in reducing the degree of osteoarthritis pain in the elderly. 17,34 The results also showed an increase in the skills of the elderly in osteoarthritis management. The increasing of knowledge affects the elderly in increasing their coping abilities.…”
Section: Discussionmentioning
confidence: 79%
“…Cognitivebehavioral therapy interventions are effective in reducing the degree of osteoarthritis pain in the elderly. 17,34 The results also showed an increase in the skills of the elderly in osteoarthritis management. The increasing of knowledge affects the elderly in increasing their coping abilities.…”
Section: Discussionmentioning
confidence: 79%
“…Additionally, pain and other symptoms have improved. Also, result is supported by (18) They showed that a self-management program improved the health status of patients with knee osteoarthritis.…”
Section: Concerning the Effect Self-management On Othermentioning
confidence: 81%
“…Ultimately, thirteen studies remained. After further reading, it was determined that they met the inclusion criteria and were included in this meta-analysis [28,[31][32][33][40][41][42][43][44][45][46][47][48] (Figure 1). 1 shows the characteristics of these 13 studies, with all included studies being RCTs.…”
Section: Study Selectionmentioning
confidence: 99%